2009
DOI: 10.1142/s0192415x09006783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Far Infrared Acupoint Stimulation on Autonomic Activity and Quality of Life in Hemodialysis Patients

Abstract: Patients receiving regular hemodialysis sessions have been known to suffer from fatigue and depression. This experiment was designed to determine the effects of far infrared ray (FIR) stimulation on acupoints of patients suffering from renal failure who are receiving regular hemodialysis. Patients receiving long-term and regular hemodialysis who volunteered for this procedure were randomly selected to undergo either FIR or heat pad (HP) therapy to determine the impact of FIR treatment on these patients. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…5 In a previous study, sauna therapy was performed using an FIR dry sauna device at 60 C for 15 min, followed by traditional warm keeping for 30 min. 6 Although previous studies have shown that FIR radiation produces thermal and non-thermal effects, such as increasing artery blood flow 7 and peripheral blood circulation, 8 improving endothelial function, 9 alleviating fatigue 10 and pain, 11 reducing blood pressure, 12 and promoting capillary dilatation, 13 the precise mechanism has yet to be thoroughly understood. Therefore, the purposes of this study were to review and summarize published data on FIR therapy on different types of diseases (Table 1) and to delineate the mechanisms of FIR therapy.…”
Section: Introductionmentioning
confidence: 99%
“…5 In a previous study, sauna therapy was performed using an FIR dry sauna device at 60 C for 15 min, followed by traditional warm keeping for 30 min. 6 Although previous studies have shown that FIR radiation produces thermal and non-thermal effects, such as increasing artery blood flow 7 and peripheral blood circulation, 8 improving endothelial function, 9 alleviating fatigue 10 and pain, 11 reducing blood pressure, 12 and promoting capillary dilatation, 13 the precise mechanism has yet to be thoroughly understood. Therefore, the purposes of this study were to review and summarize published data on FIR therapy on different types of diseases (Table 1) and to delineate the mechanisms of FIR therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, acupuncture has been used clinically to treat muscle atrophy in patients with CKD and other patients in the United States and other countries. [13][14][15] The muscle contractions elicited by LFES provide similar benefits to the patients as exercise would provide. For patients with severe CKD, this treatment may be an alternative way to achieve exercise benefits.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Studies show that acupuncture treatment can ameliorate symptoms, such as fatigue, stress, hypertension, proteinuria, and pruritus, in patients with ESRD on dialysis. [13][14][15] Acupuncture has been shown to decrease skeletal muscle atrophy induced by hind-limb suspension in mice. 16 Electrical acupuncture treatment has been shown to suppress myostatin expression, which leads to a satellite cell-related proliferative reaction and repair in skeletal muscle.…”
mentioning
confidence: 99%
“…FIR therapy can improve blood flow and survival of the arteriovenous fistula in hemodialysis patients (Lin, et al, 2007). Furthermore, FIR stimulation on acupoints at Qihai, Kuan yuan and Chung chi decreases both stress and fatigue levels as well as stimulates autonomic nervous system activity in hemodialysis patients (Su, et al, 2009). IR radiation is believed to transfer energy that is perceived as heat by thermoreceptors in the surrounding skin (Inoué & Kabaya, 1989).…”
Section: Photobiologymentioning
confidence: 99%